Perbandingan Metode FJ. Mock dan NRECA untuk Transformasi Hujan Menjadi Debit pada DAS Metro Kabupaten Malang, Jawa Timur - widyaningsih, karunia waasiu; Harisuseno, Donny; Soetopo, Widandi (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
A process of converting rain data to runoff or discharge flow is called the rain transformation process. The transformation of rain into discharge is affected by the physical characteristics of the watershed and its land used. Discharge data in a watershed functions is as a measure of the amount of discharge available in a river which is useful in improving the management of water resources. This study purpose is to determine the results of the calculation of rain to discharge which located in the Metro DAS, Malang Regency. The methods analyzed by researchers is the FJ. Mock and NRECA methods. The results of the calculation from these methods are then compared with the rain data, because the AWLR discharge in the Sub Metro Watershed is considered not suitable to be the discharge of observations in this study. Based on the analysis results, the most suitable method for calculating the rainfall discharge in the Sub Metro Watershed is NRECA method with a determination coefficient (R2) = 0.792, and a correlation coefficient (r) = 0.887. Â